Automated Irrigation and Fertigation System Applying Sensing Technology - Mahyuzie Jenal; Hakimi Zikri Nasirin; Nur Aida Nabilah Mohd Razali @ Kamaruddin; Syed Amiruddin Hilmi Sayed Mohd Al Bakir; Ummi Sorfina Rosmadi; Zureen Az Athira Z. Ahmad Rosly (Journal of Electronic Voltage and Application, 2021)
Internet of Things (IoT) is well-known and applied in all areas. The development of good agricultural systems has now become essential to address the major challenges of feeding the enormously increasing population in the agricultural sector. One way of dealing with this is to expand agricultural production standard and quantity. An integrated IoT system with irrigation and finishing on the market was missing. To make production more efficient, farmers must collect a huge amount of data from various devices. The system's effectiveness depends on the performance of the sensor in various climate changes. The network and a closed-loop feedback system need to be connected to the system to operate in maximum capacity. The Module of the Soil Moisture Sensor and the MCU ESP8266 V2 MCU Node, the float switch and the 5V Optocoupler relay module are used for this project. The remote control of the system is a mobile application. If the moisture level in the soil reaches the desired value, the results show that it stops water supply. It can translate the project on a large scale for the future project. Then the system may also be developed with solar energy rather than batteries.